2023
DOI: 10.1002/jimd.12653
|View full text |Cite
|
Sign up to set email alerts
|

Isovaleric aciduria identified by newborn screening: Strategies to predict disease severity and stratify treatment

Abstract: Newborn screening (NBS) allows early identification of individuals with rare disease, such as isovaleric aciduria (IVA). Reliable early prediction of disease severity of positively screened individuals with IVA is needed to guide therapeutic decision, prevent life‐threatening neonatal disease manifestation in classic IVA and over‐medicalization in attenuated IVA that may remain asymptomatic. We analyzed 84 individuals (median age at last study visit 8.5 years) with confirmed IVA identified by NBS between 1998 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Fortunately, the initial screening result appears to correlate with disease severity and, consequently, risk; it is notable that all 17 TP cases with initial C5C concentration < 7.2 µmol/L remained asymptomatic, whilst those requiring more intensive care demonstrated initial C5C results > 7.5 µmol/L. This is broadly comparable with the finding from the German NBS programme, where a review of 84 individuals with IVA confirmed by NBS concluded that an initial C5C concentration < 5.6 µmol/L was associated with asymptomatic disease course in most cases [20].…”
Section: Discussionsupporting
confidence: 73%
“…Fortunately, the initial screening result appears to correlate with disease severity and, consequently, risk; it is notable that all 17 TP cases with initial C5C concentration < 7.2 µmol/L remained asymptomatic, whilst those requiring more intensive care demonstrated initial C5C results > 7.5 µmol/L. This is broadly comparable with the finding from the German NBS programme, where a review of 84 individuals with IVA confirmed by NBS concluded that an initial C5C concentration < 5.6 µmol/L was associated with asymptomatic disease course in most cases [20].…”
Section: Discussionsupporting
confidence: 73%
“…Isovalerylcarnitine (C5), a carnitine derivative, is involved in fatty acid metabolism by transporting long-chain fatty acids into mitochondria for oxidation and energy production. Its levels can be in uenced by diet and metabolic status, playing a crucial role in energy metabolism [33]. Glycerol-3phosphate (G3P) is vital for growth and physiological functions in prokaryotes, plants, animals, and humans [34].…”
Section: Discussionmentioning
confidence: 99%
“…103 1D. Isovaleric Academia (IVA) [104][105][106] Isovaleric academia is an AR disorder due to the deficiency of isovaleryl-CoA dehydrogenase (IVD) required in leucine metabolism. 11 A study in Germany showed C.932C>T mutation in 47% alleles.…”
Section: Differential Diagnosismentioning
confidence: 99%